Environmental effects of marble quarry operations in Burdur Lake Basin (Burdur-Turkey) - Mehmet Ozcelik (Journal of Degraded and Mining Lands Management, 2023)
Marble is the most important natural material because of its structural features and its long durability. It is mined at operated quarries on hill slopes. The original landform is permanently altered, and vegetation cover is destroyed. Another important feature of marble quarries is the large amount of waste materials released during the quarrying process. In the last decades, together with the visible effects of global warming and climate change, fresh water resources are rapidly depleted and polluted due to careless land use. Quarrying operations are among the most important stakeholders of this process. Environmental effects of quarry activities depend on the location of the site in the landscape, the vertical and horizontal dimensions of the excavation, the methods used to excavate the marble, and the formation of the geological structure. Furthermore, the region's seismicity, microclimate conditions, ecological condition, and surface and groundwater conditions are all factors influencing environmental degradation. Additionally, numerous serious environmental impacts associated with quarrying activities near the site, such as visual pollution, water, dust, noise, air pollution, vibration, land subsidence, and landslides, will cause health issues and unpredictable biodiversity loss. Quarrying operations have the potential to impact pre-existing ecosystems, including groundwater depletion, loss of fertile topsoil, forest degradation, and human health. This article aims to draw attention to various serious environmental impacts, health problems and biodiversity loss resulting from quarrying operations in Burdur Lake Basin.